(untitled) (JOURNAL OF ANALYTICAL SYNERGY AND SCIENTIFIC HORIZON, 2025)
The article examines the main aspects of students’ adaptation to a new stage of life — the transition from school to university education. It analyzes forms of adaptation (academic, social, psychological), challenges faced by students, and the role of parents, teachers, and peers in successful adaptation. Practical recommendations, real-life case studies, and references to scientific research are provided. The conclusion emphasizes the importance of comprehensive support for students during the adaptation period.